Strength and physical activity in osteoarthritis: The mediating role of kinesiophobia. Issue 5 (6th August 2021) - Aydemir, Burcu; Huang, Chun‐Hao; Foucher, Kharma C.
Abstract: The aim of this study was to investigate the association between muscle strength and physical activity level in people with knee osteoarthritis (OA), and determine whether this association is mediated by pain‐related fear of movement (kinesiophobia) and self‐reported pain. Cross‐sectional data from 37 subjects (age 58.8 ± 8.6 years, 25F/12M, BMI 33.5 ± 6.4 kg/m 2 ) with OA of the knee were used. Isometric knee extensor and flexor muscle strength were measured using an isokinetic dynamometer. Physical activity, kinesiophobia, and pain were assessed by self‐report using the University of California, Los Angeles activity rating scale, Tampa Scale for Kinesiophobia, and The Knee Injury and Osteoarthritis Outcome Score pain subscale, respectively. The associations between strength measures, physical activity, kinesiophobia, and pain scores, were modeled by performing a parallel multiple mediation analysis and the significance of mediational effects (kinesiophobia and pain) were tested using a bootstrap approach. Lower knee flexion and extension strength were associated with lower physical activity scores and these relationships were mediated by higher kinesiophobia scores (more fear) but not pain scores. Knee extension strength was directly associated with physical activity scores after controlling for kinesiophobia and pain scores. These results suggest that muscle strength can influence physical activity directly and indirectly through fear of movement. Assessing these measures together in this population may help clinicians identify patients that are more likely to avoid physical activities due to not only muscle weakness but also fear of movement.